Editorial: Labour Market and Unemployment - Janicki, Tadeusz (Studia Historiae Oeconomicae, 2024)
Labour is a key factor of production, enabling the production of goods and services. Throughout history, the labour market situation has influenced economic growth and development, and hence investment, productivity, income, consumption and society's standard of living. The articles contained in the next volume of the journal Studia Historiae Oeconomicae analyze the above problem using selected examples dating back to the 18th century. The presented SHO volume consists of eight articles that provide authentic knowledge on such labour market shaping factors as wages, ideology and politics, as well as on the activities of labor unions and charitable organizations under different political and socio-economic systems. The study of labour and the labour market has a heavy burden for both cognitive and practical reasons, since knowledge of the causes, mechanisms and dynamics of change in this sphere can help optimize economic policies regarding the labour market as well as become a source of inspiration for readers and perhaps further research in this area.